Post-Operative Outcomes of Intravenous Lidocaine Infusion on Major Abdominal Surgery in Pediatric Patients: A Randomized Control Trial in a Tertiary Care Hospital (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Post-operative outcomes of a major abdominal surgery depend on careful & effective post-operative management. But it is a critical job especially in children. Obtaining adequate analgesia after major surgery is a problematic issue and postoperative pain still imposes a major burden of suffering in surgical patients.Objectives: The principle objectives of the study is to evaluate the effects of intravenous lidocaine infusion in pain management of pediatric population undergone in major abdominal surgery; to reduce post-operative morbidity & enhance better surgical outcome in children.Methodology: This is a randomized control trial carried out from January 2015-June2015,in a tertiary care hospital among 60 cases of 4 to 14 years children with major abdominal surgery without having any pulmonary, cardiac, hepatic or renal insufficiency. Grouping of patients that is lidocaine infusion group (Group A) and control group (Group B) was made among admitted cases for elective abdominal surgery by simple random technique by means of lottery. For assessment of postoperative pain FLACC Scale was used in both groups. Clinical examination findings & specifically designed data collection sheet with a set questionnaire were used as research instruments. Formulated data was analyzed by SPSS version 17, taking p value